Exploring a gender-responsive asset-based approach to enhance the transformative potential of value chain development in Guatemala, India and Peru - Stoian, D.; Meldrum, G.; Lamers, H.; Blare, T.; Elias, Marlène; Donovan, J. (2018)
Paper presented at the CGIAR PIM Workshop "Rural Transformation in the 21st Century: The Challenges of Low-Income, Late-Transforming Countries" held as Pre-Conference Symposium of the International Conference of Agricultural Economists in Vancouver, BC, Canada on July 28, 2018.